Collaborative Governance for Educational Eco-Tourism and Local Economic Development in Rendeng Village, Bojonegoro - Larasati Putri , Herananda Dewi; Rahaju, Tjitjik; Megawati, Suci (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
The development of educational eco-tourism has become an alternative strategy for promoting local economic growth in rural areas. This study aims to analyze the implementation of collaborative strategic governance in developing Pottery Educational Tourism (WEG) in Rendeng Village, Bojonegoro Regency, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving five key informants from the Village-Owned Enterprises (BUMDes), youth organizations, and local business actors. The results reveal that collaborative efforts between BUMDes and youth organizations play a significant role in enhancing community participation and promoting cultural-based edu-tourism. However, challenges such as limited funding, weak promotion, and inadequate infrastructure hinder the program’s long-term sustainability. The study highlights that effective strategic management through environmental observation, strategy formulation, implementation, and evaluation requires stronger institutional capacity and inter-actor collaboration. The findings contribute to the literature on collaborative governance and rural tourism management, emphasizing the importance of integrating local resources and social capital for sustainable local economic development.